Dual loop control in positioning system - Lok, Weng Hoo. (2009)
Backlash is a common phenomenon in motion control process. It happens when there is a delay between the motion on the load side and the motor side, which may lead to a loss in position accuracy and system instability. When this happens, a motion control process employing only one encoder, normally rotary encoder placed at motor position for system stability purposes, is not able to achieve load position accuracy as backlash is not accounted for in the process.